A 10-YEAR SURVEY OF DERMATOMYCOSES IN UBERABA, SOUTHEAST BRAZIL - Magalhães Gomes de Oliveira, Ana Gabriela; Batista Carneiro de Oliveira, Diego; Ferreira de Oliveira, Guilherme (Acta Biologica Brasiliensia, 2024)
Superficial fungal infections, known as dermatomycoses, are among the main dermatological pathologies and affect approximately 25% of the world’s population. Knowing the epidemiology and promoting the diagnosis of these mycoses is essential for proper treatment administration. A total of 2,325 skin, nail and hair samples were collected from all patients treated at a private clinical laboratory in the city of Uberaba - Minas Gerais - with clinical suspicion of dermatomycosis between August 2012 and July 2022 and identified using classical methodology and the VITEK®2 YST ID system. Of the collected samples, 1,327 (57.10%) were positive for fungi, of which the majority were nail samples (61.64%), followed by skin samples from the feet (14.92%) and body (11.75%). Of these, the majority were from patients between the ages of 31 and 40 years (18.23%), and the majority of scalp samples were obtained from patients up to 10 years of age (91.66%). The most frequent fungi were dermatophytes (48.61%), followed by yeasts (28.79%) and non-dermatophyte filamentous fungi (NDFF) (22.61%), and the most common species were Trichophyton rubrum (41.22%), Candida parapsilosis (13.34%), Candida albicans (7.69%) and Aspergillus sp. (6.63%). The data herein corroborate the results of the majority of studies found in the literature and highlight the importance of knowing the prevalence of the etiological agents of these mycoses so that the correct treatment can be administered and, consequently, cases of empirical prescription, recurrence and antifungal resistance can be avoided.